Genogram Visualization Using Social Network Approach For Medical Family Tree - Bokhare, Siti Fatimah (2018)
Genogram is a graphical representation of a family tree that is used for tracking family history and relationships. It provides an overview of the family history and genealogy data which allow user to clearly understand the general and complex information of their family for several generations. But, some limitations exist while using genogram, namely scalability problems while visualizing the wealth and complex information once the family tree gets bigger. Hence, a framework for exploring medical family tree data (genogram) using social network approach and analysis method as an enhancement is proposed. This framework follows the design of advanced graphical user interface guide which is the Visual Information-Seeking Mantra that is “Overview First, Zoom and Filter, then Details-on Demand”, proposed by Shneiderman in 1996. This research focuses on improving user interaction and understanding of medical family tree data. A case study has been conducted to evaluate the usefulness and ease of use of the prototype tool. It was discovered that the prototype tool which employ the social network approach improve user understanding of medical family tree in terms of usefulness and on ease of use. According to the evaluation of the proposed framework, the tool can be utilized for personal use or by healthcare professionals and furthermore it helps them to understand their medical family tree better.